2001
DOI: 10.1046/j.1365-2435.2001.00526.x
|View full text |Cite
|
Sign up to set email alerts
|

Fat stores in birds: an overlooked sink for carotenoid pigments?

Abstract: Summary 1.Carotenoids are responsible for the most striking colours in birds, but also play an important role as enhancers of the immune system. Consequently, a trade-off between the ornamental and health functions of carotenoids in birds has been proposed. 2. Although it is well known that birds can store carotenoids in different organs and tissues, including the fat stores, until now all field studies of the regulation of carotenoid stores have focused on plasma carotenoids. 3. Carotenoids in the fat of 44 w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
35
0
1

Year Published

2005
2005
2020
2020

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 48 publications
(36 citation statements)
references
References 39 publications
0
35
0
1
Order By: Relevance
“…However, although at the time of postrestriction sampling all food-deprived birds were ingesting 50% of their daily food intake (and hence 50% of carotenoids), their circulating levels of blood carotenoids decreased only by 15% with respect to prerestriction values. One possible explanation is that food-deprived birds partially compensated the reduction of carotenoids ingested by actively releasing them from body stores such as fat or liver (Negro et al 2001a). Alternatively, carotenoids stored in body fat may have been released passively to the bloodstream when fat was mobilized as a result of the decrease in food intake.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, although at the time of postrestriction sampling all food-deprived birds were ingesting 50% of their daily food intake (and hence 50% of carotenoids), their circulating levels of blood carotenoids decreased only by 15% with respect to prerestriction values. One possible explanation is that food-deprived birds partially compensated the reduction of carotenoids ingested by actively releasing them from body stores such as fat or liver (Negro et al 2001a). Alternatively, carotenoids stored in body fat may have been released passively to the bloodstream when fat was mobilized as a result of the decrease in food intake.…”
Section: Discussionmentioning
confidence: 99%
“…Alternatively, carotenoids stored in body fat may have been released passively to the bloodstream when fat was mobilized as a result of the decrease in food intake. However, to date, it is unknown whether carotenoids stored in fat can be selectively mobilized when they are required by the bird (Negro et al 2001a). Another possibility to explain the smaller than expected decrease in plasma carotenoid levels of food-deprived birds is that foodrestricted birds compensated their lower carotenoid intake by increasing their absorption efficiency.…”
Section: Discussionmentioning
confidence: 99%
“…Second, the anabolic effects of testosterone could increase the production of reactive oxygen species and hence a requirement for antioxidants. As a result, carotenoids may be liberated from major body stores such as the liver and fat (29,30) into circulation. A third possibility is that testosterone increases the absorption efficiency of ingested carotenoids (e.g., changing the activities of digestive enzymes or levels of lipoproteins), resulting also in elevated plasma levels.…”
mentioning
confidence: 99%
“…On the other hand, several experiments have also convincingly shown that expression of carotenoid ornaments depends on parasitic infections (reviewed in Hill 2002Hill , 2006Hõrak et al 2004), immune system activation (e.g., Blount et al 2003;Faivre et al 2003;McGraw and Ardia 2003), or individual nutritional state (Hill 2000;McGraw et al 2005). Other studies have also shown that birds kept on a uniform diet do not converge on the same plasma carotenoid levels (e.g., Bortolotti et al 1996;Negro et al 2001).…”
Section: Discussionmentioning
confidence: 97%